METODE TAKHRIJ HADIST: KEOTENTIKAN HADIST TENTANG ANJURAN MENIKAH - Siti Nurul Wahdatun Nafiah; Reno Kuncoro (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
The takhrij al-Hadith method is a method used to search for and trace the authenticity of a hadith by explaining in detail about the matan sanad and the quality of the hadith. In this study, the author will discuss hadiths regarding advice on marriage. This research uses literature study as a knife in reviewing, then this research uses a qualitative approach through the takhrij method with descriptive-deductive analysis. The results of this research indicate that the quality of the hadith narrated by Imam Bukhori No. 4702 regarding the recommendation that marriage has quality and is deemed authentic lidzatihi. This happened because no defects were found in the hadith transmitters, the average position of the hadith transmitters was tsiqqoh. The content in the hadith explains that the recommendation for marriage is for someone who is capable (capable here means someone is capable emotionally, socially, financially, role, sexually, spiritually and age) and wants to get married, then he should marry. Meanwhile, for someone who cannot afford it, fasting is recommended to reduce sexual pressure and control vision.